Persepsi Orang Tua Tentang Akhlak Anak Setelah Belajar di MDA Al-Muhsinin Jorong Koto Baru Simalanggang Kecamatan Payakumbuh Kabupaten Lima Puluh Kota - Ahada Dzulqa; Iswantir M; Muhiddinur Kamal; Arifmiboy Arifmiboy (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2023)
The background of this research is that parents think that MDA education is very important for them. They convey this because they are included in the category of parents who are busy working so they don't have enough time to teach their children in terms of Religious Education. That doesn't mean they let go of their responsibilities. Parents think that enrolling their children in MDA is an alternative to teach religious knowledge which they do not get in public schools. Another opinion comes from the parents who are generally housewives. They argue that putting children into MDA does nothing. This they conveyed in accordance with the results they conveyed to researchers, namely in the form of children who were still not fluent in reading the Koran and other religious education. They chose to put their children in the usual places of recitation which were usually held in small mosques taught by Garin in the mosque. These parents think their children understand religion better by putting their children in such a place.